Chemical quantification of N-acyl alanine methyl ester (NAME) production and impact on temporal gene expression patterns in Roseovarius tolerans EL-164 - Leinberger, Janina; Koteska, Diana; Boldt, Judith; Petersen, Jörn; Shivaramu, Sahana; Tomasch, Jürgen; Schulz, Stefan; Brinkhoff, Thorsten (BMC microbiology, 2024)
Previous studies have identified structurally diverse N-acyl amino acid methyl esters (NAMEs) in culture extracts of Roseovarius tolerans EL-164 (Roseobacteraceae). NAMEs are structural analogues of the common signaling compounds N-acyl homoserine lactones (AHLs), but do not participate in AHL-mediated signaling. NAMEs show minor antialgal and antimicrobial activity, but whether this activity serves as the primary ecological role remains unclear. To enable dose-dependent bioactivity-testing, we have established a chromatographic method for quantification of NAMEs in bacterial culture extracts. The concentrations determined for the two major NAMEs produced by EL-164, C16:1-NAME and C17:1-NAME, ranged between 0.685 and 5.731 mg L (2.0-16.9 µM) and 5.3-86.4 µg L (15.0-244.3 nM), respectively. Co-quantification of the C14:1-AHL showed concentrations ranging between 17.5 and 58.7 mg L (56.6-189.7 µM). We observed distinct production patterns for NAMEs and AHLs, with a continuous NAME production during the entire incubation period. We conducted a spike-in experiment, using the determined metabolite concentrations. By comparing the transcriptomes of pre- and post-metabolite-spikes, we identified three clusters of differentially expressed genes with distinct temporal expression patterns. Expression levels of stress response genes differed between NAME- and AHL-spiked EL-164 cultures in the stationary phase. Our findings support previous studies suggesting an ecological role for C16:1-NAME as antibiotic, by proving that NAME concentrations in batch cultures were higher than the minimal inhibitory concentrations against Maribacter sp. 62 - 1 (Flavobacteriia) and Skeletonema costatum CCMP 1332 (Coscinodiscophyceae) reported in the literature. Our study further exemplified the broad application range of dose-dependent testing and highlighted the different biological activities of NAMEs and AHLs.